"MLVA_5: A reduced marker scheme for phylogeographic analysis of Brucella canis" - Eduardo Jorge Boeri; Paula Becker; Silvia Noemi Akiyama; Maria Luz Dominguez; Sebastian Elena; Natalia Mercedes Fernandez; Paula Ruybal; Gabriela Ileana Escobar; Deborah Beatriz Hasan; Marcos David Trangoni (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

A predictive model developed to classify Leishmania promastigotes at two distinct life stages using MALDI-TOF mass spectrometry - Sebastian Cubides-Cely; Betsy Muñoz Serrano; Enrique Mejía-Ospino; Patricia Escobar (Archives of Microbiology, 2025)

Advances in Reproduction, Nutrition and Disease Research in the Yellowtail Kingfish ( Seriola lalandi ) Aquaculture - Alejandro S. Mechaly; Abigail Elizur; Sebastian Escobar‐Aguirre; Jorge Hirt‐Chabbert; Roxana Bertha Inohuye‐Rivera; Wayne Knibb; Josephine Nocillado; Juan C. Pérez‐Urbiola; H. K. A. Premachandra; Gustavo M. Somoza; Dariel Tovar‐Ramírez; Bin Wang (Reviews in Aquaculture, 2025)
Yellowtail kingfish ( Seriola lalandi ) is a species of significant value in aquaculture, with a broad distribution across subtropical and temperate seas. Although global production has doubled in 7 years, reaching approximately 9000 tons per year in 2021, its cultivation remains limited compared to other mainstream species. The commercial aquaculture of this species faces several key challenges in achieving improved production and sustainability: nutrition requirements, disease management, and the optimization of reproductive technologies. Current diets for yellowtail kingfish require further improvement to enhance both growth performance and sustainability. Diseases continue to be a major constraint, with at least 41 specific diseases reported for yellowtail kingfish and 31 affecting other Seriola species, emphasizing the necessity of targeted diagnostic tools and treatment strategies. Recent genomic advances have shed light on the biology and taxonomy of yellowtail kingfish, revealing genetically distinct populations across the South Pacific, Indian, and South Atlantic Oceans. However, the taxonomic status within the Pacific region remains unclear, requiring further research. Addressing these gaps is vital for developing robust breeding programs and improving genetic resilience. To support the sustainable expansion of yellowtail kingfish aquaculture, key areas for future research include increasing larval and juvenile survival rates, minimizing malformations, and tailoring farming models to diverse environmental conditions. Focusing on these priorities will ensure better productivity and disease resistance, ultimately promoting the global competitiveness of yellowtail kingfish as an aquaculture species.

Late Miocene-early Pliocene hydroclimate evolution of the western Altiplano, northern Chile: Implications for aridification trends under warming climate conditions - Carlie Mentzer; Carmala Garzione; Carlos Jaramillo; Luis Felipe Hinojosa; Jaime Escobar; Nataly Glade; Sebastian Gomez; Deepshikha Upadhyay; Aradhna Tripati; Kaustubh Thirumalai (Global and Planetary Change, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Effect of CRISPR/Cas9 Targets Associated with Iron Metabolism and Its Variation on Transcriptional Regulation of SHK-1 Cell Line as a Model for Iron Metabolism - Phillip Dettleff; Yehwa Jin; Carolina Peñaloza; Rodrigo Pulgar; Alejandro Sáez; Diego Robledo; Sebastian Escobar-Aguirre (Fishes, 2024)
In this study, we investigated the function of a gene associated with iron metabolism using CRISPR-Cas9 and RNA sequencing in SHK-1 salmon cells. Our objective was to understand how different guide RNA (gRNA) sequences against the transferrin gene tf could influence gene expression and cellular processes related to iron uptake. RNA-Seq analysis was performed to evaluate the transcriptomic effects of two distinct gRNA targets with high knock-out (KO) efficiencies for the targeted tf gene in the SHK-1 genome. Our results showed no significant differential expression in transferrin-related transcripts between wild-type and CRISPR-edited cells; however, there were major differences between their transcriptomes, indicating complex transcriptional regulation changes. Enrichment analysis highlighted specific processes and molecular functions, including those related to the nucleus, cytoplasm, and protein binding. Notably, different sgRNAs targeting tf might result in different mutations at DNA levels in SHK-1 salmon cells.

The taste of colours - Carlos Velasco; Francisco Barbosa Escobar; Charles Spence; Juan Sebastian Olier (Food Quality and Preference, 2023)

Transfer of β-lactam and tetracycline antibiotics from spiked bovine milk to Dambo-type cheese, whey, and whey powder - Daniela Escobar Gianni; Ronny Pelaggio; Gonzalo Cardozo; Sebastian Moreno; Elena De Torres; Fabiana Rey; Inés Martínez; Gonzalo Suarez Veirano; Laura Olazabal (Food Additives & Contaminants: Part A, 2023)

A dynamic 2DH flocculation model for coastal domains - Sebastian Escobar; Qilong Bi; Michael Fettweis; Samor Wongsoredjo; Jaak Monbaliu; Erik Toorman (Ocean Dynamics, 2023)

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Key Drivers for Non-Centrifugal Sugar Cane Research, Technological Development, and Market Linkage: A Technological Roadmap Approach for Colombia - Diego Hernando Flórez-Martínez; Carlos Alberto Contreras-Pedraza; Sebastian Escobar-Parra; Jader Rodríguez-Cortina (Sugar Tech, 2023)
Food science innovation depends on consumers’ needs and is currently seeking functional food with health effects. Non-centrifugal cane sugar (NCS) is known for its potential health effects, but there is a lack of holistic analysis on technological advancement and socio-economic and market trends for decision-making in the development of the technology. The aim of this article was to analyse the research trends, recent patents, and market trends and niches for NCS to structure an NCS technological roadmap. Scientometric, bibliometric methods, and global and local market information on NCS were used. Comprehensive analysis of the worldwide research trends and patents on NCS processing and of the growth of the main niche markets for Colombian NCS exports in the last five years was conducted. Finally, with the information obtained, an NCS technological roadmap was structured, which can be used as a tool for planning innovation processes and supporting the development of new research using market information and new norms forged by the COVID-19 pandemic for Colombian case. Furthermore, the methodological design could be used for other NCS producer countries.

‘From soil to chocolate bar’: identifying critical steps in the journey of cadmium in a Colombian cacao plantation - Daniel Bravo; Margareth Santander; Jader Rodríguez; Sebastian Escobar; Gideon Ramtahal; Rachel Atkinson (Food Additives & Contaminants: Part A, 2022)

Editorial: Sustainable Development Goal 14 - Life Below Water: Towards a Sustainable Ocean - Brett W. Molony; Alex T. Ford; Ana M. M. Sequeira; Angel Borja; Anna Milena Zivian; Carol Robinson; Christian Lønborg; Elva G. Escobar-Briones; Emanuele Di Lorenzo; Jesper H. Andersen; Marius N. Müller; Michelle J. Devlin; et al. (Frontiers in Marine Science, 2022)

An overview of the physical and biochemical transformation of cocoa seeds to beans and to chocolate: Flavor formation - Margareth Santander Muñoz; Jader Rodríguez Cortina; Fabrice Eric Vaillant; Sebastian Escobar Parra (Critical Reviews in Food Science and Nutrition, 2020)